(untitled) (In Factis Pax: Journal of Peace Education and Social Justice, 2010)
The title for this paper comes from a participant in a study that I recently conducted comparing war resisters and war veterans from the Vietnam era. Hardy, a warresister, moved to Canada in 1967 in opposition to the Vietnam War. When I was interviewing Hardy about his decision to move to Canada, he made a distinction between“good” Americans and “bad” Americans. He described a good American as “someone who is proud of their country and it’s my country right or wrong,” and a bad American as one who will “question and will want to debate and would follow principles as opposed to policies.” His description of good and bad Americans in the context of the Vietnam War has relevance for today’s society, especially when considering the values and beliefs for democratic citizenship.